2011
DOI: 10.3354/meps09317
|View full text |Cite
|
Sign up to set email alerts
|

Rocky intertidal temperature variability along the southeast coast of Australia: comparing data from in situ loggers, satellite-derived SST and terrestrial weather stations

Abstract: Predicting how both spatial and temporal variation in sea and air temperature influence the distribution of intertidal organisms is a pressing issue. We used data from satellites, weather stations and in situ loggers to test the hypothesis that satellite-derived sea surface temperatures (SSTs) and weather station air temperatures provide accurate estimates of ambient temperature variability on rocky intertidal shores for temporal (hourly for 1 yr) and spatial (10 m to 400 km) variation along the southeast coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
4
34
0
4
Order By: Relevance
“…The findings of this study are consistent with previous studies that have compared in situ temperature data from intertidal (Lathlean et al, 2011), subsurface (Pearce et al, 2006), and shallow waters (Smale and Wernberg, 2009;Stobart et al, 2016) with satellite SST data. However, all of these studies used either the closest satellite pixel to their study location (Malcolm et al, 2011;Baldock et al, 2014), an average of all the satellite data within an arbitrary distance (e.g., 20 km 2 box centered on logger location: Stobart et al, 2016), or number of pixels (Delgado et al, 2014) from the logger locations.…”
Section: Satellite-derived Temperaturessupporting
confidence: 82%
See 2 more Smart Citations
“…The findings of this study are consistent with previous studies that have compared in situ temperature data from intertidal (Lathlean et al, 2011), subsurface (Pearce et al, 2006), and shallow waters (Smale and Wernberg, 2009;Stobart et al, 2016) with satellite SST data. However, all of these studies used either the closest satellite pixel to their study location (Malcolm et al, 2011;Baldock et al, 2014), an average of all the satellite data within an arbitrary distance (e.g., 20 km 2 box centered on logger location: Stobart et al, 2016), or number of pixels (Delgado et al, 2014) from the logger locations.…”
Section: Satellite-derived Temperaturessupporting
confidence: 82%
“…SST, however, may not be available for coastal areas due to contamination in the satellite-derived images [noisier radar returns from land and sea (Brooks et al, 1990) and improper instrument corrections (Shum et al, 1998)]. In addition, previous studies have demonstrated biases in SST data when comparing it to in situ measurements within coastal areas (Smale and Wernberg, 2009;Lathlean et al, 2011;Stobart et al, 2016), with some studies recording up to 6 • C differences (Smit et al, 2013). These biases are due to contamination of the satellite processing due to the presence of coastal features such as the shoreline, estuaries and embayments as well as complex coastal dynamics such as tides and upwelling (Smit et al, 2013) that vary over short spatial scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em costões rochosos, a utilização de sensores eletrônicos de temperatura, instalados em um gradiente vertical no mediolitoral, possibilita a medição contínua da variação de temperatura no micro-habitat, na tentativa de correlacioná-las às mudanças na estrutura da população, mais comumente de bivalves e cirrípedes, e aos dados ambientais que expliquem o comportamento termal desses organismos (Helmuth, 2002;Siviero, 2010;Lathlean et al, 2011). Mortalidade causada por estresse térmico depende não apenas da frequência de eventos de alta temperatura, mas também da taxa de aquecimento e resfriamento experimentado pelos organismos (Denny et al 2006) que, no caso dos sésseis ou sedentários, será determinada pelo horário das marés baixas, pelo grau de exposição às ondas e pelo clima (Harley & Helmuth, 2003;Harley, 2008;Mislan et al, 2009).…”
Section: Introductionunclassified
“…Mortalidade causada por estresse térmico depende não apenas da frequência de eventos de alta temperatura, mas também da taxa de aquecimento e resfriamento experimentado pelos organismos (Denny et al 2006) que, no caso dos sésseis ou sedentários, será determinada pelo horário das marés baixas, pelo grau de exposição às ondas e pelo clima (Harley & Helmuth, 2003;Harley, 2008;Mislan et al, 2009). Portanto, tentativas para prever o efeito de mudanças da temperatura em organismos do mediolitoral requerem medições in situ (Lathlean et al, 2011).…”
Section: Introductionunclassified